Nomogram to predict 5-year global cognitive impairment in de novo Parkinson disease with normal cognition at baseline - Wang, Xin; Tian, Lu (Frontiers in Neuroscience, 2025)
Background and objectiveCognitive impairment (CI, combing mild cognitive impairment and dementia) seriously affects the quality of life in patients with de novo Parkinson disease (PD). The aim of the present study was to identify the potential predictive factors for 5-year cognitive decline in de novo PD.MethodsParkinson’s Progression Marker Initiative (PPMI) database was retrieved and PD patients with normal global cognition at baseline were included. These patients were divided into normal cognitive (NC) group and CI group based on their Montreal Cognitive Assessment (MoCA) scores at the 5-year follow-up period. A total of 66 baseline variables were compared between these two groups. Univariate and multivariate logistic regression analyses were conducted, followed by the development and validation of a nomogram to predict 5-year global cognitive decline in de novo PD patients.ResultsA total of 344 PD patients with normal baseline cognition were included, in which 73 individuals developed CI at the 5 year follow-up period. Baseline MoCA, Benton Judgment of Line Orientation (BJOLO), Hopkins Verbal Learning Test (HVLT) immediate recall, Letter Number Sequencing (LNS), Symbol-Digit Modalities Test (SDMT), Semantic Fluency Test (SFT) scores, and Scale for Outcomes in Parkinson’s disease for Autonomic symptoms (SCOPA-AUT) total, gastrointestinal, and sexual dysfunction scores were selected out from the 66 potential predictors based on logistic regression analysis. These predictors were finally included in the nomogram of the model. The area under the ROC curve of the model was 0.870 (95% CI, 0.825–0.915).ConclusionOur study constructed a model that predicts 5-year cognitive decline in de novo PD with high accuracy, which may allow for the early risk stratification of future CI in PD patients at baseline.